Are the thyroid and adrenal system alterations linked in depression? - Mokrani, Marie-Claude; Duval, Fabrice; Erb, Alexis; Gonzalez Lopera, Felix; Danila, Vlad (Psychoneuroendocrinology, 2020)
•Thyrotropin (TSH) and cortisol secretions are not linked in depressed patients.•Nyctohemeral profiles of TSH, and TSH responses to 0800 h and 2300 h protirelin (TRH) tests are independent of DST status.•These results indicate that in most depressed inpatients HPT and HPA axis abnormalties can occur independently. Disturbances in the hypothalamic-pituitary-thyroid (HPT) and hypothalamic-pituitary-adrenal (HPA) axes have been frequently found in major depression. Given that glucocorticoids may inhibit thyrotropin (TSH) and thyrotropin-releasing hormone (TRH) secretion, it has been hypothesized that hypercortisolemia could lead to HPT axis abnormalities. So far, data on interactions between the HPA and HPT axes in depression remain inconclusive. In order to investigate this issue, we examined circadian rhythms of serum TSH and cortisol (sampled at 4 -hly intervals throughout a 24 -h span), TSH responses to 0800 h and 2300 h protirelin (TRH) tests and cortisol response to dexamethasone suppression test (DST) in 145 unmedicated inpatients meeting DSM-IV criteria for major depressive disorder (MDDs) and 25 healthy hospitalized control subjects (HCs). The secretion of TSH and cortisol exhibited a significant circadian rhythm both in HCs and MDDs. However, compared to HCs, MDDs showed: 1) reduced TSH mesor and amplitude values; 2) blunted 2300 h-ΔTSH and ΔΔTSH values (i.e. differences between 2300 h and 0800 h TRH-TSH responses); and 3) increased cortisol mesor and post-DST cortisol values. DST nonsuppresssors (n = 40, 27 %) showed higher cortisol mesor than DST suppressors (n = 105, 73 %). There was no difference between DST suppressors and nonsuppressors in their TSH circadian parameters and TRH-TSH responses. In addition, cortisol values (circadian and post-DST) were not related to TRH test responses. Our results do not confirm a key role for hypercortisolemia in the HPT axis dysregulation in depression.